I never do this : a novel - Miller, Anesa (Sibylline Press, 2024)
"LaDene Faye Howell grew up in the small town of Devola on an oxbow of the Muskingum River in southeast Ohio. Her conservative family is deeply religious, although another branch of the Howell clan are notorious criminals. When one of her outlaw relatives returns from prison, LaDene hopes the two of them may share an evening of fun, or even a spark of romance. Instead, Bobby Frank embroils her in kidnapping their old high school principal. Taken into custody, LaDene recounts her misadventures in the form of a dramatic monologue. Pledging to "tell all in full truth" she hopes to keep herself out of jail and perhaps even soften Bobby's likely sentence. She aims to capture her listeners' sympathy by recounting a history she has never shared before: her teenage pregnancy and confinement at an unforgiving evangelical facility for wayward girls."--